2014
DOI: 10.1073/pnas.1318469111
|View full text |Cite
|
Sign up to set email alerts
|

Navigability of interconnected networks under random failures

Abstract: Assessing the navigability of interconnected networks (transporting information, people, or goods) under eventual random failures is of utmost importance to design and protect critical infrastructures. Random walks are a good proxy to determine this navigability, specifically the coverage time of random walks, which is a measure of the dynamical functionality of the network. Here, we introduce the theoretical tools required to describe random walks in interconnected networks accounting for structure and dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
402
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 431 publications
(408 citation statements)
references
References 43 publications
3
402
1
2
Order By: Relevance
“…As an example, we have applied it also to social 17 and economical systems, coauthorship networks 36 , metropolitan transportation networks 24 and continental air transportation systems 20 (see Table 1). A particularly interesting case is that of the FAO (Food and Agriculture Organization of the United Nations) worldwide food import/export network, an economic network in which layers represent products, nodes are countries and edges at each layer represent import/export relationships of a specific food product among countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, we have applied it also to social 17 and economical systems, coauthorship networks 36 , metropolitan transportation networks 24 and continental air transportation systems 20 (see Table 1). A particularly interesting case is that of the FAO (Food and Agriculture Organization of the United Nations) worldwide food import/export network, an economic network in which layers represent products, nodes are countries and edges at each layer represent import/export relationships of a specific food product among countries.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in biological systems basic constituents such as proteins can have physical, co-localization, genetic or many other types of interactions. Recently, it has been shown that retaining such multi-dimensional information 7 and modelling the structure of interdependent and multilayer systems respectively through interdependent 8 and multilayer networks [9][10][11][12] reveals new nontrivial structural properties [13][14][15][16][17][18][19][20] and relevant emergent physical phenomena [21][22][23][24][25][26][27] .…”
mentioning
confidence: 99%
“…Interconnected networks are mathematical representations of systems where two or more simple networks, possibly with different functionalities, are coupled to each other. The omnipresence of interconnected networks has spurred a variety of research [4][5][6][7], with particular interest in dynamical processes such as percolation [8,9], epidemic spreading [10][11][12][13], and diffusion [14,15].…”
mentioning
confidence: 99%
“…As mentioned above diffusion dynamics on networks can be studied analytically using transition matrices of random walkers [8,9]. The multi-layer structure of a network can explicitly be incorporated in a random walk model by constructing a so-called supra-transition matrix [3,12] similar to the supra-adjacency matrix used in [9,10,11].…”
Section: Multi-layer Networkmentioning
confidence: 99%
“…The multi-layer structure of a network can explicitly be incorporated in a random walk model by constructing a so-called supra-transition matrix [3,12] similar to the supra-adjacency matrix used in [9,10,11]. The supra-adjacency matrix of a multi-layer network G can be defined in a block-matrix structure as…”
Section: Multi-layer Networkmentioning
confidence: 99%